Making Use of Home Equity: The Potential of Housing Wealth to Enhance Retirement Security - Jorge Miguel Bravo; Mercedes Ayuso; Robert Holzmann (Institute of Labor Economics (IZA), 2019)
The demographic change underway, declining adequacy levels from traditional pay-as-you-go old-age social security systems, structural reforms in pension schemes and the reduction in the traditional family support have increased the need for additional private savings to cover the old age income gap. In this paper we discuss the necessity, the role and the viability of home equity release schemes in supplementing public and private pensions in an integrated way. We use the latest European data from the Eurosystem Household Finance and Consumption Survey (HFCS) to analyse the household's wealth composition and accumulation process in the euro area. To quantify the size of the housing wealth and its potential to enhance existing and future retirement income, we compute the equity-to-value ratio (ETV) for all countries, estimate the time to loan payoff and compute the amount of home equity that is expected to be released over a 10-year period through regular monthly mortgage payments. We then catalogue and discuss the many alternative options for managing and accessing housing wealth over the life cycle, and highlight the main characteristics, risks, advantages and drawbacks of the two most important market products (home reversion plans and reverse mortgages). Finally, we discuss the main demand-side and supply-side obstacles and challenges to the development of equity release markets and extract some policy implications.
Keywords: D1; G1; J1; R2; R3; 330; equity release schemes; housing wealth; reverse mortgage; homeownership; retirement income; pensions adequacy